Sustainable carbon-based Cu/Zn catalysts for the water gas shift reaction - Cordero-Alcántara, Tomás; Rivas-Márquez, María Nerea; Riquelme-García, Paula; Ruiz-Rosas, Ramiro Rafael; Navlani, Miriam; Rosas-Martínez, Juana María; Cazorla-Amorós, Diego; Rodríguez-Mirasol, José (My University, 2025)
Hydrogen is a versatile energy carrier, which provides a viable pathway toward sustainable development. Among the various existing production routes, the water gas shift (WGS) reaction is fundamental to producing high purity H2 and is widely used in a few industrial applications. However, its efficiency is highly dependent on the type of catalyst. In this context, the search for more active, stable, and sustainable materials has gained relevance, highlighting the use of alternative supports to alumina such as activated carbons derived from lignocellulosic biomass.
Keywords: Hidrógeno; Catalizadores; Carbón activado; Copper/zinc catalysts; Activated carbons; Hydrogen